Effect of warming and acidification on polar lipid fatty acid composition in juvenile European sea bass (Dicentrarchus labrax) - Romain Gonzalvez; Mickaël Péron; Margaux Mathieu-Resuge; Fabienne Le Grand; Mishal Cohen-Rengifo; Sophie Collet; Philippe Soudant; Marie Vagner (Marine Environmental Research, 2026)

Response to visual and mechano-acoustic predator cues is robust to ocean warming and acidification and is highly variable in European sea bass - Mishal Cohen-Rengifo; David Mazurais; Marie-Laure Bégout (Frontiers in Marine Science, 2023)
Predator-prey interactions and, especially, the success of anti-predator responses are modulated by the sensory channels of vision, olfaction, audition and mechanosensation. If climate change alters fish sensory ability to avoid predation, community dynamics can be affected. We investigated whether mid-duration exposure to warming and/or acidification alters behavioural response to visual or mechano-acoustic predator cues in juvenile Dicentrarchus labrax . We measured kinematic variables before and after a visual or a mechano-acoustic challenge which mimicked an overflying bird shadow or a bird swoop attack, respectively. Due to large interindividual variability in responses before cue presentation, fish were categorized as slow and fast to account for baseline individual variability. Treatment did not impact kinematic variables as both slow and fast fish of every treatment elicited precautionary and escape responses. Interestingly, even slow fish swam as fast as fast fish after the cue, suggesting that regardless of initial category, fish managed to escape facing a danger. Anti-predator response varied according to the level of threat to survival with greater responses elicited after the swoop attack. Although wild juvenile sea bass aggregate in schools, school dynamics rely on single leaders which highlights the importance of the variability in individual behaviours. We demonstrated that anti-predator response in juvenile D. labrax is robust to mid-duration exposure to independent and combined effects of warming and acidification. If robustness is confirmed over long-duration, it could provide D. labrax with an evolutionary advantage in the future ocean, where cue transmission through changing environments can further modulate cue perception and predator-prey interactions.

Attachment capacity of the sea urchin Paracentrotus lividus in a range of seawater velocities in relation to test morphology and tube foot mechanical properties - Mishal Cohen-Rengifo; Claire Moureaux; Philippe Dubois; Patrick Flammang (Marine Biology, 2017)

Robustness of Paracentrotus lividus larval and post-larval development to pH levels projected for the turn of the century - Eliseba García; José Carlos Hernández; Sabrina Clemente; Mishal Cohen-Rengifo; Celso Agustín Hernández; Sam Dupont (Marine Biology, 2015)